The genus Bulbothrix (Parmeliaceae) in China. (19th February 2016) - ZHANG, Yan Yun; WANG, Xin Yu; LIU, Dong; SHI, Hai Xia; YE, Xin; YANG, Mei Xia; WANG, Li Song
Abstract: The morphology, chemistry and phylogenetic relationships of Chinese populations of Bulbothrix are described. Nine species, including two new species B. mammillaria Y. Y. Zhang & Li S. Wang sp. nov. and B. lacinia Y. Y. Zhang & Li S. Wang sp. nov., and two newly recorded for the flora, B. scortella and B. meizospora, are reported. Bulbothrix mammillaria can be recognized by the sparse cilia that are reduced to a bulbate structure and the broad lobes (3–11 mm). Bulbothrix lacinia differs from other species of the genus by dark brown, spherical to short-cylindrical isidia and common lacinulae on the upper surface. Phylogenetic relationships of currently known ITS sequences from Bulbothrix were inferred to assess the affinities of the new species. A key to all known species from China is presented.